Entrepreneurship, economic conditions, and the great recession - Robert W. Fairlie (University of California, Economics Department, 2011)
The Great Recession resulted in many business closings and foreclosures, but what effect did it have on business formation? On the one hand, recessions decrease potential business income and wealth, but on the other hand they restrict opportunities in the wage/salary sector leaving the net effect on entrepreneurship ambiguous. The most up-to-date microdata available - the 1996 to 2009 Current Population Survey (CPS) - are used to conduct a detailed analysis of the determinants of entrepreneurship at the individual level to shed light on this question. Regression estimates indicate that local labor market conditions are a major determinant of entrepreneurship. Higher local unemployment rates are found to increase the probability that individuals start businesses. Home ownership and local home values for home owners are also found to have positive effects on business creation, but these effects are noticeably smaller. Additional regression estimates indicate that individuals who are initially not employed respond more to high local unemployment rates by starting businesses than wage/salary workers. The results point to a consistent picture - the positive influences of slack labor markets outweigh the negative influences resulting in higher levels of business creation. Using the regression estimates for the local unemployment rate effects, I find that the predicted trend in entrepreneurship rates tracks the actual upward trend in entrepreneurship extremely well in the Great Recession.
Keywords: L26; 330; Entrepreneurship; Great Recession; Unemployment; Self-Employment